The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1111/ctr.12039
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of vitamin D status in long‐term renal transplant patients

Abstract: In this study, we explored the determinants of vitamin D status in a large cohort of stable, Long-term renal transplant (RTx) patients. Serum 25(OH)D concentrations, and bone biochemistry parameters, were retrospectively analyzed from 266 RTx patients (>10 yr post-engraftment) presenting to clinic over the course of a year. Forty-five percent of the cohort were vitamin D deficient (<37.5 nM), 38% insufficient (37.5 75-nM), and 17% sufficient (>75 nM). Serum 25(OH)D concentrations were higher in patients presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…Time from transplantation seems to positively influence 25-OH-D level in which every year out of transplantation decreases the risk of deficiency by approximately 10% [27] . In addition to the reduced sunlight exposure, the use of sun protectors, and the impaired kidney function, the use of immunosuppressive drugs especially high doses of steroid, and the presence of metabolic syndrome and obesity are also associated with 25OHD deficiency [26,28] ; Lower 25OHD level in KT recipients can worsen the degree of hyperparathyroidism by depleting the substrate for 1,25dihydroxyvitamin D (1,25OH2D) production [25] . Severe 1,25OH2D deficiency can be observed in up to 80% in the immediate posttransplant period [29] .…”
Section: Vitamin Dmentioning
confidence: 99%
“…Time from transplantation seems to positively influence 25-OH-D level in which every year out of transplantation decreases the risk of deficiency by approximately 10% [27] . In addition to the reduced sunlight exposure, the use of sun protectors, and the impaired kidney function, the use of immunosuppressive drugs especially high doses of steroid, and the presence of metabolic syndrome and obesity are also associated with 25OHD deficiency [26,28] ; Lower 25OHD level in KT recipients can worsen the degree of hyperparathyroidism by depleting the substrate for 1,25dihydroxyvitamin D (1,25OH2D) production [25] . Severe 1,25OH2D deficiency can be observed in up to 80% in the immediate posttransplant period [29] .…”
Section: Vitamin Dmentioning
confidence: 99%
“…Among patients undergoing KT, studies have been conducted during different periods of the year, making it difficult to know whether they follow the trend observed in the general population. The literature commonly describes parathyroid hormone stimulation due to 25(OH)D deficiency during the earliest periods after KT as a consequence of the high doses of corticosteroids and persistent elevation of phosphatonins 6,18,19. Some authors have also found this correlation during later periods of KT recovery 7,20.…”
Section: Discussionmentioning
confidence: 99%
“…This radiation is clearly the most important physical environmental carcinogen for the development of skin cancer, and non-melanoma skin cancer (NMSC) is the most common malignancy among patients undergoing KT 23,24. The risk of developing this complication is associated with the duration and intensity of immunosuppression and cumulative sun exposure 18. However, some guidelines suggest that sunlight exposure for short periods of time is beneficial and does not increase the risk of skin cancer 25,26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These seasonal cyclical VitD results suggest there may be poor compliance with sun avoidance behaviours despite repeated reminders to avoid sunlight, sunbathing and to use sun protection (hats, gloves, creams) [20]. This asymmetrical seasonality response to VitD repletion, with winter repletion associated with inadequate restoration of 25(OH)D, indicates that structured dose-adjustments are probably required to optimize the repletion regimen.…”
Section: Discussionmentioning
confidence: 99%